Shale Oil and Shale Gas Resources - Torres, José A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This multidisciplinary book covers a wide range of topics addressing critical challenges for advancing the understanding and management of shale oil and shale gas resources. Both fundamental and practical issues are considered. By covering a variety of technical topics, we aim to contribute to building a more integrated perspective to meet major challenges faced by shale resources. Combining complementary techniques and examining multiple sources of data serve to advance our current knowledge about these unconventional reservoirs. The book is a result of interdisciplinary and collaborative work. The content includes contributions authored by active scientists with ample expertise in their fields. Each article was carefully peer-reviewed by researchers, and the editorial process was performed by an experienced team of Senior Editors, Guest Editors, Topic Editors, and Editorial Board Members. The first part is devoted to fundamental topics, mostly investigated on the laboratory scale. The second part elaborates on larger scales (at near-wellbore and field scales). Finally, two related technologies, which could be relevant for shale plays applications, are presented. With this Special Issue, we provide a channel for sharing information and lessons learned collected from different plays and from different disciplines.